The iconosphere of contemporary terrorism in the perspective of visual arts - Zydorowicz, Jacek (Humaniora. Czasopismo Internetowe, 2020)
The perspective on terrorism adopted in the paper Visual Culture in the Age of Terrorism is closest to visual studies in the field of cultural studies. Discussions on the topic of visual studies over the last decades have so far resulted in numerous publications and commentaries, but one can have the impression that more than enough they constituted meta-narratives describing research methods rather than implementations of these methods. Meanwhile, research methods appear to be very adequate tools of cultural analysis, in which the component of visual communication is gaining significance. After WWII, it is terrorism and its iconosphere that have prov`en to be the most distinct examples of visual communication. The paper’s aim is to present the images whose source or topic is terrorism and in particular it is about the cultural regimes of production and decoding of these images. The images are culturally framed in line with the iconological tradition, and so the way in which they are interpreted, assigned meaning and studied according to their impact on the field requires some sensitization to cultural contexts, constant consultations between various practices, discourses and disciplines, looking straight ahead and sideways, and sometimes from different perspectives simultaneously.